1994
DOI: 10.1055/s-0038-1642522
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of Rabbit Heparin Cofactor II: A Plasma Thrombin Inhibitor Highly Conserved between Species

Abstract: SummaryHeparin cofactor II (HCII), a circulating plasma protein that inhibits thrombin, is a member of the serine proteinase (serpin) family of proteins. The extent to which HCII structure is conserved actross species lines was investigated, by obtaining cDNA clones encoding rabbit HCII. Overlapping clones corresponding to rabbit HCII were obtained by the combined use of hybridization screening of a rabbit liver cDNA library, and by rapid amplification of cDNA ends (RACE). The consensus sequence obtained spans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…We have chosen to use deletion mutagenesis to map the minimum essential form of HCII that is sufficient for complex formation with thrombin. HCII was selected over AT because of its lack of disulphide bonding, and because we have recently demonstrated that its expression in rabbit reticulocyte lysate systems yields a more functional product than that of AT [14]. Our results suggest that the helix A structural element is an essential part of a functional serpin.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…We have chosen to use deletion mutagenesis to map the minimum essential form of HCII that is sufficient for complex formation with thrombin. HCII was selected over AT because of its lack of disulphide bonding, and because we have recently demonstrated that its expression in rabbit reticulocyte lysate systems yields a more functional product than that of AT [14]. Our results suggest that the helix A structural element is an essential part of a functional serpin.…”
Section: Introductionmentioning
confidence: 75%
“…Transcription plasmids were transcribed in vitro from phage promoters; the A169, 106, and 58 constructs using T 7 polymerase, and the A81 construct using SP 6 polymerase, as described previously [14]. Translation was performed as described [14,18], in a messenger-dependent reticulocyte lysate supplemented with [35S]methionine.…”
Section: In Vitro Transcription and Translationmentioning
confidence: 99%
See 3 more Smart Citations